2016
DOI: 10.1186/s12891-016-0961-7
|View full text |Cite
|
Sign up to set email alerts
|

Five year results of the first ten ACL patients treated with dynamic intraligamentary stabilisation

Abstract: BackgroundIn recent years, the scientific discussion has focused on new strategies to enable a torn anterior cruciate ligament (ACL) to heal into mechanically stable scar tissue. Dynamic intraligamentary stabilization (DIS) with LigamysTM was first performed in a pilot study of 10 patients. The purpose of the current study was to evaluate the five year results of this group.MethodsInclusion criteria were an ACL rupture not older than 14 days, patient age <45 years, no previous surgery on the injured knee, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 14 publications
7
77
0
Order By: Relevance
“…Among them, seven articles were clinical studies and 11 articles were animal studies. Of the 7 clinical studies, there were 5 level Ⅳ case-series studies, 2 , 15 , 16 , 17 , 18 1 level Ⅲ retrospective case-control studies 19 and 1 level Ⅲ cohort study 20 ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, seven articles were clinical studies and 11 articles were animal studies. Of the 7 clinical studies, there were 5 level Ⅳ case-series studies, 2 , 15 , 16 , 17 , 18 1 level Ⅲ retrospective case-control studies 19 and 1 level Ⅲ cohort study 20 ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 18 , a Case series 69 42:27 32.4 ≥24 Microfracturing Sutures and DIS 2.9% Instrumented SSD: 2.3 mm Lysholm: 97, Tegner: 5.1, IKDC: 94.8 10 Eggli et al. 15 Case series 10 8:2 23.3 60.3 Microfracturing Sutures and DIS 20% Instrumented SSD: 2 mm Lysholm: 100, Tegner: 5.5, IKDC: 98.9 10 Murray et al. 20 Cohort Study: 10 Control: 10 6:14 24 3 BEAR scaffold Suture 0% Study group vs control group Lachman test: 8 grade A, 2 grade B vs 10 grade A IKDC: 54.3 vs 60.7 20 M, male; F, female; mo, months; yr, year; F/U, follow-up; d, day; mo, month NP, not provided; HRT, healing response technique; DIS, dynamic intraligamentary stabilization.…”
Section: Resultsmentioning
confidence: 99%
“…The minimum follow-up was 12 months, with a mean follow-up of 21 months (range, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. All the patients underwent surgery within 3 weeks after injury.…”
Section: Methodsmentioning
confidence: 99%
“…Advantages of this technique include preservation of the native ligament with its proprioceptive nerve fibers and the lack of donor site morbidity because no graft harvesting is necessary. Recent studies have shown that this ACL preserving technique achieves good clinical mid-term results with high functional scores and patient satisfaction [1][2][3][4][5]. However, the revision rate in the current literature ranges from 2.8% to 20.0% depending on the follow-up period, cohort, and, most importantly, the definition of revision itself, which is not uniformly defined throughout the different studies [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The goals of this study were, therefore, the following: (1) to determine the frequency of revision and non-revision reinterventions after DIS treatment; and (2) to analyze the different types of revision and non-revision reinterventions and the associated reasons. We hypothesized that: (1) the revision rate was in the range of published results after ACL reconstructions; and (2) non-revision reinterventions were performed more frequently.…”
Section: Introductionmentioning
confidence: 99%